(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In today’s competitive world, every enterprise strives to increase the efficiency of its production in order to achieve financial stability in the market and obtain higher profits. One of the ways to achieve this position is to optimize the composition and cost accounting. The correct choice of the cost accounting method will ensure control over the composition and rational use of the resources available in the organization. The article discusses modern systems of cost accounting and calculating the cost of production. Their conditions of application in various industries, the main advantages and disadvantages are considered.